Risk of death during and after opiate substitution treatment in primary care: prospective observational study in UK General Practice Research Database. (26th October 2010) - Cornish, Rosie; Macleod, John; Strang, John; Vickerman, Peter; Hickman, Matt
Abstract : Objective To investigate the effect of opiate substitution treatment at the beginning and end of treatment and according to duration of treatment. Design Prospective cohort study. Setting UK General Practice Research Database Participants Primary care patients with a diagnosis of substance misuse prescribed methadone or buprenorphine during 1990-2005. 5577 patients with 267 003 prescriptions for opiate substitution treatment followed-up (17 732 years) until one year after the expiry of their last prescription, the date of death before this time had elapsed, or the date of transfer away from the practice. Main outcome measures Mortality rates and rate ratios comparing periods in and out of treatment adjusted for sex, age, calendar year, and comorbidity; standardised mortality ratios comparing opiate users' mortality with general population mortality rates. Results Crude mortality rates were 0.7 per 100 person years on opiate substitution treatment and 1.3 per 100 person years off treatment; standardised mortality ratios were 5.3 (95% confidence interval 4.0 to 6.8) on treatment and 10.9 (9.0 to 13.1) off treatment. Men using opiates had approximately twice the risk of death of women (morality rate ratio 2.0, 1.4 to 2.9). In the first two weeks of opiate substitution treatment the crude mortality rate was 1.7 per 100 person years: 3.1 (1.5 to 6.6) times higher (after adjustment for sex, age group, calendar period, and comorbidity) than the rate during the rest of time on treatment. The crude mortality rate was 4.8 per 100 person years in weeks 1-2 after treatment stopped, 4.3 in weeks 3-4, and 0.95 during the rest of time off treatment: 9 (5.4 to 14.9), 8 (4.7 to 13.7), and 1.9 (1.3 to 2.8) times higher than the baseline risk of mortality during treatment. Opiate substitution treatment has a greater than 85% chance of reducing overall mortality among opiate users if the average duration approaches or exceeds 12 months. Conclusions Clinicians and patients should be aware of the increased mortality risk at the start of opiate substitution treatment and immediately after stopping treatment. Further research is needed to investigate the effect of average duration of opiate substitution treatment on drug related mortality.